Wildfire hazards, risks, and disasters - Paton, Douglas; Buergelt, Petra T.; McCaffrey, Sarah; Tedim, Fantina; Shrober, John F. (Hazards and disasters series, 2015)
More than 90% of wildfires are caused by human activity, but other causes include lighting, drought, wind and changing weather conditions, underground coal fires, and even volcanic activity. Wildfire Hazards, Risks, and Disasters, one of nine volumes in the Elsevier Hazards and Disasters series, provides a close and detailed examination of wildfires and measures for more thorough and accurate monitoring, prediction, preparedness, and prevention